2006
DOI: 10.1111/j.1574-695x.2006.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila (Chlamydia) pneumoniaein the Alzheimer's brain

Abstract: We assessed the presence and characteristics of the intracellular pathogen Chlamydophila (Chlamydia) pneumoniae in brain-tissue samples from 25 patients with late-onset Alzheimer's disease (AD) and 27 non-AD control individuals. 20/ 27 AD patients, but only 3/27 controls, were PCR-positive in multiple assays targetting the Cpn1046 and Cpn0695 genes. Culture of the organism from braintissue homogenate from one AD patient, and assessment of various chlamydial transcripts in RNA preparations from several patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(182 citation statements)
references
References 56 publications
11
163
0
Order By: Relevance
“…In this respect, there is evidence suggesting that some relationship exists between the APOE4 gene product and the pathobiology of the intracellular Chlamydophila (Chlamydia) pneumoniae involved in AD pathogenesis [8,9]. Moreover, the risk of developing AD is much greater in patients HSV-1-positive in brain who also possess an APOE4 allele than in those with only one of these factors [29].…”
Section: And 2 Years After Treatment In Patients For Whommentioning
confidence: 99%
“…In this respect, there is evidence suggesting that some relationship exists between the APOE4 gene product and the pathobiology of the intracellular Chlamydophila (Chlamydia) pneumoniae involved in AD pathogenesis [8,9]. Moreover, the risk of developing AD is much greater in patients HSV-1-positive in brain who also possess an APOE4 allele than in those with only one of these factors [29].…”
Section: And 2 Years After Treatment In Patients For Whommentioning
confidence: 99%
“…Positive association Wndings obtained in brain tissues from patients with AD and controls are strengthened by the fact that the investigators were blinded for the disease status at least in some studies which showed association between AD and Cpn, rendering false positive results e.g. by contamination or observer bias unlikely [20,22]. However, the signiWcance of these Wndings is tempered by the fact that the tissue samples were not additionally analyzed by independent laboratories and could not be reconWrmed in other studies.…”
Section: Discussionmentioning
confidence: 87%
“…In another study, they reported that by amplifying two diVerent chlamydial target genes Cpn0695 and Cpn1046, 20 out of 25 (80%) samples of patients with AD compared to 3 out of 27 (11.1%) samples of the control group were Cpn-DNA positive [22]. Using immunohistochemical staining, they observed a co-localization of Cpn with amyloid plaques and NFTs, two of the major pathophysiological correlates of AD [22].…”
Section: Evidence For Involvement Of Chlamydia Pneumoniae Infection Imentioning
confidence: 91%
See 1 more Smart Citation
“…This intracellular bacterium has been found at high incidence in the brains of AD patients by PCR and immunohistochemistry [96]. C. pneumoniae has also been found localized in nerve cells in close proximity to neurofibrillary tangles, a characteristic of AD [96,97].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%